2016
DOI: 10.1186/s12890-016-0252-y
|View full text |Cite
|
Sign up to set email alerts
|

Miliary pulmonary nodules due to Mycobacterium xenopi in a steroid-induced immunocompromised patient successfully treated with chemotherapy: a case report

Abstract: BackgroundMycobacterium xenopi-infected patients have a high prevalence of pulmonary cavities and nodules. However, the clinical course for patients with miliary nodules due to M. xenopi has not yet been reported.Case presentationWe encountered a case of miliary nodules with gradually worsening coughing and sputum production in a 44-year-old male who had renal dysfunction due to glomerulosclerosis with a decade-long history of steroid therapy. Although we started anti-tuberculosis treatment on clinical suspici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In a half of the patients with M. xenopi pulmonary disease, initial pulmonary radiographic changes are unilateral and cavitary changes are present in 96% 15 . While our finding is in concordance with this classical presentation of fibrocavitary disease, a recent study highlighted marked proportion of nodulary pattern changes, which were also present in the latest Japanese case report, suggesting dissemination of the disease in an immunocompromised patient under steroid treatment 16,22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a half of the patients with M. xenopi pulmonary disease, initial pulmonary radiographic changes are unilateral and cavitary changes are present in 96% 15 . While our finding is in concordance with this classical presentation of fibrocavitary disease, a recent study highlighted marked proportion of nodulary pattern changes, which were also present in the latest Japanese case report, suggesting dissemination of the disease in an immunocompromised patient under steroid treatment 16,22 .…”
Section: Discussionsupporting
confidence: 92%
“…In 1994, Terashima et al 23 reported two cases of pulmonary disease caused by M. xenopi -one occurred after gastrectomy and the other synchronously with M. tuberculosis infection, both presented with features of an infectious disease and unilateral cavitary lesion at chest x-rays 23 . Several cases of Japanese authors have been reported thereafter 22,24 . While all the firstly mentioned isolates were susceptible to streptomycin and kanamycin, the later results highlighted importance of drug susceptibility testing on disease outcome and levofloxacin as potential antibiotic with proven M. xenopi susceptibility in the presented cases 24 .…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Mycobacterium xenopi. Clinical and radiological disease manifestations of M. xenopi infection vary according to the patient's immunological status and can be classified into three groups: a cavitary form in patients with preexisting pulmonary disease, a solitary nodular form in immunocompetent patients, and an acute infiltrate form in immunosuppressed patients (73). M. xenopi lung disease usually develops in individuals with chronic obstructive pulmonary disease or bronchiectasis with an apical cavitary radiological appearance.…”
Section: Novel Species or Subspecies (Reference) C Yr Of Descriptionmentioning
confidence: 99%
“…The fact that bacillus Calmette-Guerin (BCG) immunotherapy for bladder cancer sometimes induces systemic granulomatous inflammation supports the hypothesis that HTL is an allergic reaction rather than an infection (40,41). In addition, the possibility of endobronchial spread of NTM (M. xenopi) was reported in an immunocompromised patient (42).…”
Section: Miliary Pulmonary Opacitiesmentioning
confidence: 85%